The building blocks of preschool success / Katherine A. Beauchat, Katrin L. Blamey, Sharon Walpole. - Beauchat, Katherine A.
Written expressly for preschool teachers, this engaging book explains the ""whats,"" ""whys,"" and ""how-tos"" of implementing best practices for instruction in the preschool classroom. The authors show how to target key areas of language and literacy development across the entire school day, including whole-group and small-group activities, center time, transitions, and outdoor play. Detailed examples in every chapter illustrate what effective instruction and assessment look like in three distinct settings: a school-based pre-kindergarten, a Head Start center with many English language learners, and a private suburban preschool. Helpful book lists, charts, and planning tools are featured, including reproducible materials.